2019
DOI: 10.1039/c9dt02714a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the intramolecular magnetic interactions in the highly saddled iron(iii) porphyrin π-radical cations: the change from planar to saddle conformations

Abstract: The intramolecular magnetic interactions in one-electron oxidized iron(iii) porphyrin π-radical cations with planar and saddle conformations have been compared by means of a variety of spectroscopic, physical methods and unrestricted DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Due to the fact that 2 reacts with C–H substrates in a HAT mechanism, it can be assumed that the product of HAT is a Fe III porphyrin-π-cation radical 3 (thus [Fe III (Cl) 2 (T­(OMe)­PP•)] or isomers thereof, for example [Fe IV (Cl) 2 (T­(OMe)­PP)]). , We targeted the synthesis of this compound by substochiometric reaction of 1 with the one-electron oxidant (Phenox. )­SbCl 6 in the presence of a Cl – source ( n Bu 4 NCl) at +20 °C in DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that 2 reacts with C–H substrates in a HAT mechanism, it can be assumed that the product of HAT is a Fe III porphyrin-π-cation radical 3 (thus [Fe III (Cl) 2 (T­(OMe)­PP•)] or isomers thereof, for example [Fe IV (Cl) 2 (T­(OMe)­PP)]). , We targeted the synthesis of this compound by substochiometric reaction of 1 with the one-electron oxidant (Phenox. )­SbCl 6 in the presence of a Cl – source ( n Bu 4 NCl) at +20 °C in DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Their averages were 14 (3 OE ) and 20 (3 OM ) ppm further upfield than those of oneelectron-oxidized [Fe(OE(M)TPP * )Fe III Cl] + and [(OE-(M)TPP * )Fe III Br] + complexes, revealing less spin density resided in their respective d x 2 À y 2 orbitals (Figures S8, S9). [31,32] These saddle-shaped porphyrin macrocycles behaved as redox non-innocent ligands; thus, exact differentiation of isoelectronic products, including Fe IV -oxo porphyrin and the Fe III porphyrin radical, was challenging. Nevertheless, 3 OE should possess more Fe IV characteristics than the aforementioned highspin Fe III porphyrin radicals do.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous DFT studies have indicated that the Fe III (d z 2 , d x 2 À y 2 )-porphyrin (a 2u ) interactions in fivecoordinate saddled high-spin and intermediate-spin Fe III porphyrins are stronger than the planar d z 2 -a 2u interactions; in addition, greater saddling deformation is associated with stronger d x 2 À y 2 /d z 2 -a 2u interaction. [32,34] To understand how such saddle-induced orbital interactions accelerate OÀ O homolysis, we employed DFT calculations based on the ZORA-B3LYP/TZ2P//BP86-D3/TZP and ZORAÀ S12 g/ TZ2P//BP86-D3/TZP levels, including COSMO/CH 2 Cl 2 , implemented in the ADF program to examine the homolytic OÀ O bond cleavage of the 5-coordinate Fe III -OOR species to Fe IV -oxo species, via an OÀ O bond breaking transition state (i. e., 2 OM ! TS_2 OM !3 OM and 2 OE !TS_3 OE !3 OE ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations